2019
DOI: 10.1002/ece3.4976
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic changes during caste development through social interactions in the termite Zootermopsis nevadensis

Abstract: One of the most striking examples of phenotypic plasticity is the different phenotypes (i.e., castes) within a same nest of social insects. Castes usually derive from a single genotype initially by receiving social cues among individuals during development. Specific gene expression changes may be involved in caste differentiation, and thus, the regulatory mechanism of these changes should be clarified in order to understand social maintenance and evolution. The damp‐wood termite Zootermopsis nevadensis is one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…After topical application of JHA on pseudergates of H. sjostedti, the JH titer decreased at first, but gradually increased and reached the plateau just before the pseudergate-presoldier molt [5]. According to our RNA-Seq results, the JH synthesis pathway is the most significantly enriched pathway, which was consistent with the RNA-Seq study in Z. nevadensis [42]. The changes of expression profiles of the JH synthesis genes were also documented in Z. nevadensis [43].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…After topical application of JHA on pseudergates of H. sjostedti, the JH titer decreased at first, but gradually increased and reached the plateau just before the pseudergate-presoldier molt [5]. According to our RNA-Seq results, the JH synthesis pathway is the most significantly enriched pathway, which was consistent with the RNA-Seq study in Z. nevadensis [42]. The changes of expression profiles of the JH synthesis genes were also documented in Z. nevadensis [43].…”
Section: Discussionsupporting
confidence: 89%
“…The upregulation of those metabolic pathways reflected the histological change after the application of JHA. The enrichment of metabolic pathways was also reported in Z. nevadensis [42]. The fat body plays an important role in insect metamorphosis.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In phenotypic plasticity in insects, some studies suggested the interconnection between insulin and Hippo/Toll pathways (Cassa & Moczek, 2018; Gotoh et al, 2015). In an incipient colony of Z. nevadensis , KEGG analysis showed that the Hippo pathway was upregulated in the first offspring individual that becomes the first soldier (Yaguchi, Suzuki, Matsunami, Shigenobu, & Maekawa, 2019). Taken together, there should be some crosstalks among JH, ecdysone, insulin, and other physiological signaling pathways including Hippo/Toll pathway, and the coordination of these pathways is suggested to determine caste fates, leading to the expressions of caste‐specific phenotypes.…”
Section: Insulin Signalingmentioning
confidence: 99%
“…Some important genes, such as hexamerin 8 , insulin receptor 12 , distal-less 9 and deformed 13 , 14 have been found to be specifically expressed at a certain point during the molting period (i.e., worker-presoldier molt). Furthermore, some specifically expressed genes and cascades have been identified during the differentiation of the first soldier in an incipient colony 15 17 , based on the genome sequences of the primitive termite Zootermopsis nevadensis 18 . However, even in Z. nevadensis, there are no artificial induction methods of caste differentiation other than those for soldiers, therefore, comprehensive gene expression patterns and comparative transcriptome profiles among caste differentiations are not fully understood.…”
Section: Introductionmentioning
confidence: 99%